Deteksi Kelompok Enterobacteriaceae pada Tanah di Lingkungan Tempat Pembuangan Akhir Sampah Tamangapa Kecamatan Manggala Makassar - Tuty Widyanti; Andi Fatmawati (Jurnal Ilmu Alam dan Lingkungan, 2022)
Garbage is one of the problems faced, especially in big cities throughout developed and developing countries which can lead to environmental pollution such as soil pollution. Soil that contains many sources of pollutants from waste allows bacteria to live in that place, both pathogenic and non-pathogenic bacteria such as Coliform bacteria, where their presence is an indicator of biological environmental pollution. This does not rule out the possibility of finding other pathogenic bacteria such as bacteria from the Enterobacteriaceae group such as Salmonella, Shigella, Escherichia coli, Klebsiella, Enterobacter, Serratia, Proteus, etc. which cause infectious diseases in the digestive tract. This study used soil samples taken in 5 environmental areas of the Tamangapa Final Disposal Site in the District, Manggala Makassar randomly. The purpose of the study was to detect groups of Enterobactericeae in the soil in the Tamangapa Final Disposal Site in the district, Manggala Makassar. This study uses an identification method based on biochemical tests automatically using the VITEK 2TM Compact, bioMérieux, SA tool. Based on the research that has been carried out, the results obtained are that there are types of bacteria of the Enterobacteriaceae group detected in the environmental soil of the Tamangapa Final Disposal Site in the District, Manggala Makassar, namely Enterobacter cloacae, Klebsiella pneumonia, and Escherichia coli which are classified as species that cause pathogenic diseases of the digestive tract